2020
DOI: 10.1097/brs.0000000000003383
|View full text |Cite
|
Sign up to set email alerts
|

More Than 10-year Follow-up After Laminoplasty and Pedicle Screw Fixation for Cervical Myelopathy Associated With Athetoid Cerebral Palsy

Abstract: Study Design. Retrospective case series. Objective. The aim of this study was to investigate the clinical outcomes >10 years following laminoplasty and pedicle screw fixation for cervical myelopathy associated with athetoid cerebral palsy (CP). Summary of Background Data. Surgery for cervical myelopathy associated with CP remains a challenge because of perioperative instrumentation failure and adjacent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…To evaluate the clinical functions for patients with cervical myelopathy associated with athetoid CP, it might be difficult to use the JOA score system because it assesses the neurological function of these patients [17]. In the current study, we used the BI to evaluate the ADL of patients with CP [7,12]. The JOA scores of overall patients were not significantly improved; however, the BI improved significantly after surgery.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…To evaluate the clinical functions for patients with cervical myelopathy associated with athetoid CP, it might be difficult to use the JOA score system because it assesses the neurological function of these patients [17]. In the current study, we used the BI to evaluate the ADL of patients with CP [7,12]. The JOA scores of overall patients were not significantly improved; however, the BI improved significantly after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…For the surgical strategy, spinal instrumented fusion is generally recommended for cervical myelopathy associated with athetoid CP due to the involuntary neck movements and cervical instability [5][6][7][8]. Regarding complications related to fusion surgery, it has been reported that more than 90% of the patients show disc degeneration of the adjacent segment of the fusion site and some patients have to undergo additional fusion surgery, and 23% of patients show adjacent diseases with recurrent myelopathy after previous fusion surgery with a mean interval of 8 years [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the incidence of complications, the clinical outcome is another important factor used to assess the postoperative prognosis. Demura et al [ 3 ] showed that the 10-year Barthel index and JOA score after cervical surgery significantly improved (by 36% and 31%, respectively) in 14 patients with CSM and CP. Additionally, Watanabe et al [ 29 ] reported that the JOA score improved from 8.3 points preoperatively to 10.9 points by the final follow-up (mean, 58 months) in patients with cervical disorder-associated CP who underwent posterior fusion using cervical pedicle screws; however, one-third of the patients were unable to walk at the final follow-up owing to myelopathy progression.…”
Section: Discussionmentioning
confidence: 99%